Porcelain decoration design, tableware shape construction and surface location schemes for pattern - Brants, Inese (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
My pedagogic work as a porcelain painting teacher brought to my attention the problems of connecting two-dimensional painting or decor with three-dimensional shape. This paper presents my research on the contradictions between porcelain decor and shape and provides insight into shape construction of objects and, consequently, shape designer’s contribution to tableware design. Understanding of tableware shape structure is equally helpful for the artists creating decoration designs and for the museum researchers describing collection items. By selecting and analyzing the images of porcelain decoration of different time periods, the basic principles of pattern organizing and decoration layout that follows shape design can be determined. The study used qualitative and selective methods of research, including visual material selection and interpretation. The visual material for the analyses was collected in The Museum of the History of Riga and Navigation, Riga Porcelain Museum, The Art Museum Riga Bourse, Victoria and Albert Museum in London, Sèvres Ceramics Museum in Paris, The State Hermitage Museum in St. Petersburg, Herend Porcelain Museum in Hungary and Augarten Porcelain Museum in Vienna.